Relationship of speed-strength and anthropometric indicators of highly qualified football players 16-17 years of different roles - Kalinin E.M. ,; Savin D.N. ,; Kuzmichev V.A. ,; Leksakov A.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the relationship between the anthropometric and speed-strength characteristics of football players in laboratory and field conditions to identify differences in these indicators relative to their role. Methods and structure of the study. An examination of the players of the Russian youth football team aged 16-17 years was carried out. In laboratory conditions, the players' body composition, isometric strength of the hip adductor and abductor muscles were measured; the strength of the extensor muscles of the leg joints when performing an upward jump with the arm squatting on the belt; hamstring strength in eccentric, yielding, mode. 6 hours later, during an evening training session, the players performed 10, 20 and 30 m runs and a standing long jump. Results and conclusions. As a result of the experiment, a profile of speed-strength readiness of highly qualified football players aged 16-17 years was obtained. Sports selection of taller, heavier players under 17 years of age, and generally better physically fit, may have an advantage in the short term, but in the long term there is a risk of weeding out talented.